2016
DOI: 10.1155/2016/2765821
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of Steel Columns under Load: Torsional-Flexural Buckling

Abstract: The paper presents experimental and numerical research into the strengthening of steel columns under load using welded plates. So far, the experimental research in this field has been limited mostly to flexural buckling of columns and the preload had low effect on the column load resistance. This paper focuses on the local buckling and torsional-flexural buckling of columns. Three sets of three columns each were tested. Two sets corresponding to the base section (D) and strengthened section (E) were tested wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…1a). [2] Unterweger suggests the use of modified buckling reduction factor κ * referred to the base section. He also proposes use of reduction of the ultimate load due to welding by about 12 % although the welding usually creates favourable residual stress distribution [3].…”
Section: Methodsmentioning
confidence: 99%
“…1a). [2] Unterweger suggests the use of modified buckling reduction factor κ * referred to the base section. He also proposes use of reduction of the ultimate load due to welding by about 12 % although the welding usually creates favourable residual stress distribution [3].…”
Section: Methodsmentioning
confidence: 99%
“…Vild and Bajer [36][37][38][39] conducted several experimental and numerical studies on the strengthening of steel columns using welded plates. The tests that focused on the local buckling and torsional-flexural buckling of columns [36,37] indicated that the average ultimate load capacity of the columns strengthened under load was similar to and even slightly higher than that of columns strengthened without preloads. The investigations of columns failing through flexural buckling [38,39] indicated that the ultimate load capacity of steel columns strengthened under load was decreased by the preload but only slightly.…”
Section: Marzouk and Mohanmentioning
confidence: 99%
“…Considering only the experimental tests in the literature, five types of sections were investigated: H-shaped sections (comprised of two steel channels and a plate) strengthened by bolting four plates to the inside of the flanges [26], welded H-shaped sections strengthened by welding cover plates onto the flanges [27,32,34,35,38,39], H-shaped sections transformed into box sections by welding steel plates [39], T-shaped sections transformed into uniaxial symmetric H-shaped sections by welding a new flange [36,37], and steel angles strengthened by welding additional angles [41]. Some tests indicated that the preload was unfavorable [35,38,39], some indicated that the effect of the preload was negligible [26,27,32,34,41], while others indicated that the preload slightly increased the ultimate load capacity [36,37]. Furthermore, among the aforementioned papers, only O'Sullivan [26] investigated columns strengthened using bolting, and all the other researches focused on strengthening by welding.…”
Section: Marzouk and Mohanmentioning
confidence: 99%
“…They offered optimized profiles in terms of dimensions while maintaining the appropriate value of slips. In addition, the FEM method is used to determine torsional flexural buckling in steel columns, expanded in [12], and to analyse the braking system of the friction crane described in [13]. The authors in [14,15] present the operation of safety gears as a result of changing operating conditions and based on experimental studies carried out wavelet analysis of the results obtained.…”
Section: Introductionmentioning
confidence: 99%